Ciguatoxins activate specific cold pain pathways to elicit burning pain from cooling - Vetter, Irina; Touska, Filip; Heß, Andreas; Hinsbey, Rachel; Sattler, Simon; Lampert, Angelika; Sergeeva, Marina; Sharov, Anastasia; Collins, Lindon S.; Eberhardt, Mirjam; Engel, Matthias; Cabot, Peter J.; et al. (EMBO Journal, 2012)
Ciguatoxins are sodium channel activator toxins that cause ciguatera, the most common form of ichthyosarcotoxism, which presents with peripheral sensory disturbances, including the pathognomonic symptom of cold allodynia which is characterized by intense stabbing and burning pain in response to mild cooling. We show that intraplantar injection of P-CTX-1 elicits cold allodynia in mice by targeting specific unmyelinated and myelinated primary sensory neurons. These include both tetrodotoxin-resistant, TRPA1-expressing peptidergic C-fibres and tetrodotoxin-sensitive A-fibres. P-CTX-1 does not directly open heterologously expressed TRPA1, but when co-expressed with Na v channels, sodium channel activation by P-CTX-1 is sufficient to drive TRPA1-dependent calcium influx that is responsible for the development of cold allodynia, as evidenced by a large reduction of excitatory effect of P-CTX-1 on TRPA1-deficient nociceptive C-fibres and of ciguatoxin-induced cold allodynia in TRPA1-null mutant mice. Functional MRI studies revealed that ciguatoxin-induced cold allodynia enhanced the BOLD (Blood Oxygenation Level Dependent) signal, an effect that was blunted in TRPA1-deficient mice, confirming an important role for TRPA1 in the pathogenesis of cold allodynia. © 2012 European Molecular Biology Organization | All Rights Reserved.
CRIS-Team Scopus Importer:2025-03-24
Keywords: ciguatoxin; cold allodynia; Nav; nociceptor; TRPA1